(untitled) (Research, Society and Development, 2021)
This article aimed to identify the main indicators, laws and policies implemented by each of the countries in Latin America and to analyze, in a comparative way, the implementation of the deliberations signed with the global commitments related to the end of AIDS. This is an ecological analytical observational study, whose data came from the public domain information directories of the Laws and Policies website of UNAIDS, tabulated in Excel 2016®, carried out frequency calculations and descriptive statistical analysis using software BioStat®. The countries that most contemplated the recommendations of laws and policies for responses to HIV / AIDS were Brazil (79.6%) and Mexico (74%). The countries that least adapted their laws and policies to the recommendations of the global commitment were Peru (29.6%), Venezuela (44.4%) and Bolivia (44.4%). There were considerable discrepancies in the adoption of the laws and policies recommended by UNAIDS, with a positive highlight for Brazil and Mexico compared to other Latin American countries.